Neoadjuvant Therapy of DOF Regimen Plus Bevacizumab Can Increase Surgical Resection Ratein Locally Advanced Gastric Cancer: A Randomized, Controlled Study. Issue 42 (October 2015) - Ma, Junxun; Yao, Sheng; Li, Xiao-Song; Kang, Huan-Rong; Yao, Fang-Fang; Du, Nan
Abstract : Abstract: Locally advanced gastric cancer (LAGC) is best treated with surgical resection. Bevacizumab in combination with chemotherapy has shown promising results in treating advanced gastric cancer. This study aimed to investigate the efficacy of neoadjuvant chemotherapy using the docetaxel/oxaliplatin/5-FU (DOF) regimen and bevacizumab in LAGC patients. Eighty LAGC patients were randomized to receive DOF alone (n = 40) or DOF plus bevacizumab (n = 40) as neoadjuvant therapy before surgery. The lesions were evaluated at baseline and during treatment. Circulating tumor cells (CTCs) were counted using the FISH test. Patients were followed up for 3 years to analyze the disease-free survival (DFS) and overall survival (OS). The total response rate was significantly higher in the DOF plus bevacizumab group than the DOF group (65% vs 42.5%, P  = 0.0436). The addition of bevacizumab significantly increased the surgical resection rate and the R0 resection rate ( P  < 0.05). The DOF plus bevacizumab group showed significantly greater reduction in CTC counts after neoadjuvant therapy in comparison with the DOF group ( P  = 0.0335). Although the DOF plus bevacizumab group had significantly improved DFS than the DOF group (15.2 months vs 12.3 months, P  = 0.013), the 2 groups did not differ significantly in OS (17.6 ± 1.8 months vs 16.4 ± 1.9 months, P  = 0.776. Cox proportional model analysis showed that number of metastatic lymph nodes, CTC reduction, R0 resection, and neoadjuvant therapy are independent prognostic factors for patients with LAGC. Neoadjuvant of DOF regimen plus bevacizumab can improve the R0 resection rate and DFS in LAGC. These beneficial effects might be associated with the reduction in CTC counts.